STUDI KEBERHASILAN INVESTOR DALAM BERINVESTASI SAHAM DI BURSA EFEK INDONESIA - Sumantyo, Riwi; Saputro, Arry Budi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2019)
This research has an aim to determine the factors that influence the success of an investor in stock investments in Surakarta city, Central Java. The variables studied are investor experience, the time in which stocks are sold, education level and total capital. The data collection is conducted through interviews, utilizing questionnaires, and direct observations with a total sample of 90 investors which were selected using the proportional random sampling technique. The analysis tool utilized in this study is the multiple linear regression analysis The research results showed the four variables, investor experience, time in which stocks are sold, education level, and the total capital, individually have a positive on the investors’ success in stock investments in Indonesia Stock Exchange. The variable with the greatest influence on the investor’s stock investments success in Indonesia Stock Exchange is the capital. The recommendations are investors must participate in stock analysis trainings, both fundamental and technical to reduce risks, investors are suggested to never place 100% of their investments in the same stock portfolio and instead diversify it with other assets, further studies should encompass other variables that may influence the success of investors in stock investments. Securities companies are expected and authority to provide comfortability, risk considerations, and benefit, as well as security for investors’ funds Keywords: investor’s success, investor’s experience, the time before stocks are sold, education level, and total capital, proportional random sampling classification.
Keywords: the success of investor, the experience of investors, the length of the sale of stock, the level of education and the amount of capital, classified proportional random sampling